Sodium-ion battery positive electrode material, preparation method, sodium-ion battery and electric equipment
By adopting a perovskite-structured LaNixCryMzO3 shell in the sodium ion battery positive electrode material and adding Ni and Cr elements at the B position to form a highly entropy single-phase solid solution, the problem of the oxidation of sodium ion layered oxide positive electrode material after desodium desodium is solved, and the structural stability of the material and the cycling performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411957794.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The oxidation of sodium ion layered oxide positive electrode material increases after desodium desodium and is prone to chemical and electrochemical reactions with the electrolyte, resulting in material loss of oxygen and dissolution of transition metals, affecting electrochemical and cycling properties.
The sodium ion battery positive electrode material of the LaNixCryMzO3 shell with a perovskite structure is used to form a highly entropy single-phase solid solution to improve the structural stability of the material by blending Ni and Cr elements at the B position and other transition metal elements into the shell.
On the premise of ensuring conductivity and electrochemical activity, the structural stability of the positive electrode material is significantly improved, the resistance to electrolyte corrosion is enhanced, the discharge specific capacity and capacity retention rate are improved, and the safety and cycle stability of the battery are improved.
Smart Images

Figure CN119786557A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery positive electrode material, a preparation method, a sodium ion battery, and electrical equipment. Background Art
[0002] When the sodium-ion layered oxide cathode material is de-sodiumized, its oxidizability increases, and it is very easy to react chemically and electrochemically with the electrolyte, resulting in the material losing oxygen and the dissolution of transition metals. Especially at high voltage, the electrolyte may be oxidized to produce H + , which increases the acidity of the electrolyte, destroys the surface film of the electrode material, changes the interface composition and structure, and seriously affects the electrochemical performance and cycle performance of the material. In view of this, a sodium ion battery positive electrode material with better comprehensive performance is particularly necessary. Summary of the invention
[0003] The purpose of the present invention is to provide a sodium ion battery positive electrode material, a preparation method, a sodium ion battery, and electrical equipment to improve the comprehensive performance of the positive electrode material.
[0004] The present invention is achieved in that:
[0005] In a first aspect, the present invention provides a sodium ion battery positive electrode material, comprising a core and an outer shell, wherein the core is a sodium ion layered oxide, and the outer shell comprises LaNi with a perovskite structure. x Cr y M z O 3 , wherein 0.2≤x≤0.5, 0.2≤y≤0.5, 0≤z≤0.5, x+y+z=1, and M is selected from at least one transition metal element.
[0006] In an optional embodiment, M is selected from at least one of Sc, Ti, V, Mn, Fe, Co, Cu, and Zn.
[0007] In an alternative embodiment, M is selected from at least one transition metal ion having a positive trivalence.
[0008] In an optional embodiment, the positive electrode material satisfies at least one of the following conditions:
[0009] (1) The mass ratio of the shell to the core is 1.0wt% to 3wt%;
[0010] (2) The thickness of the shell is 50 nm to 200 nm;
[0011] (3) The mass fraction of residual hydroxide in the positive electrode material is less than 0.1 wt %.
[0012] In an optional embodiment, the chemical formula of the sodium ion layered oxide is Na a Ni i Fe j Mn k N 1-i-j- k O 2 , wherein 0.8≤a≤1.1, 0.2≤i≤0.3, 0.1≤j≤0.2, 0.4≤k≤0.5, and N is selected from at least one of Cu, Zn, Sn, Ti, Co, Al, Zr, Y, Ca, Li, Rb, Cs, W, Ce, Mo, Ba, Mg, Ta, Nb, V, Sc, Sr, and B elements.
[0013] In a second aspect, the present invention provides a method for preparing a positive electrode material for a sodium ion battery, wherein a first mixture including a core material and a shell material is first calcined to obtain the positive electrode material; wherein the shell material includes LaNi with a perovskite structure x Cr y M z O 3 , wherein 0.2≤x≤0.5, 0.2≤y≤0.5, 0≤z≤0.5, x+y+z=1, and M is selected from at least one transition metal element.
[0014] In an optional embodiment, the positive electrode material satisfies at least one of the following conditions:
[0015] a. The first calcination temperature is 400 ℃-800 ℃, and the time is 5h-20h;
[0016] b. The heating rate of the first calcination is 1°C / min-5°C / min;
[0017] c. The core material comprises a sodium ion layered oxide;
[0018] Optionally, the chemical formula of the sodium ion layered oxide is Na a Ni i Fe j Mn k N 1-i-j-k O 2 , wherein 0.8≤a≤1.1, 0.2≤i≤0.3, 0.1≤j≤0.2, 0.4≤k≤0.5, and N is selected from at least one of Cu, Zn, Sn, Ti, Co, Al, Zr, Y, Ca, Li, Rb, Cs, W, Ce, Mo, Ba, Mg, Ta, Nb, V, Sc, Sr, and B;
[0019] d. The M is selected from at least one of Sc, V, Cr, Mn, Fe, Co, and Ni;
[0020] e. The M is selected from at least one transition metal ion having a positive trivalence.
[0021] In an optional embodiment, the method for preparing the shell material comprises: mixing metal oxides including La, Ni, Cr and M and performing a second calcination to obtain the LaNi perovskite structure. x Cr y M z O 3 , wherein M is selected from at least one transition metal element;
[0022] Optionally, the second calcination is performed at a temperature of 650° C.-1100° C. and for a time of 5 h-20 h.
[0023] In a third aspect, the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in any one of the aforementioned embodiments, or the sodium ion battery positive electrode material prepared by the method for preparing the sodium ion battery positive electrode material described in any one of the aforementioned embodiments.
[0024] In a fourth aspect, the present invention provides an electrical device comprising the sodium ion battery described in the aforementioned embodiment.
[0025] The present invention has the following beneficial effects:
[0026] In the sodium ion battery positive electrode material provided by the present invention, the shell comprises a perovskite structure (ABO 3 ) x Cr y M z O 3 , wherein 0.2≤x≤0.5, 0.2≤y≤0.5, 0≤z≤0.5, x+y+z=1, and M is selected from at least one transition metal element. 3 The simultaneous addition of Ni and Cr elements at the B position in the shell can provide the shell with good conductivity and corrosion resistance, thereby improving the structural stability of the positive electrode material while ensuring that the positive electrode material of the sodium ion battery has good conductivity and electrochemical activity.
[0027] When Ni and Cr elements are doped into the B position and other transition metal elements are added at the same time, the shell material can be made high-entropy, and the shell material is more inclined to form a single-phase solid solution, which is beneficial to further improve the structural stability of the shell material, and then improve the structural stability of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 is a SEM image of the core material of Example 1;
[0030] Figure 2 This is a SEM image of the sodium ion battery positive electrode material of Example 1;
[0031] Figure 3 This is a cross-sectional SEM image of the sodium ion battery positive electrode material of Example 1;
[0032] Figure 4 is the XRD pattern of the core material of Example 1;
[0033] Figure 5 1 to 4 are XRD diagrams of the sodium ion battery positive electrode materials of Examples 1 to 4. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0035] The embodiment of the present invention provides a sodium ion battery positive electrode material, comprising a core and an outer shell, wherein the core is a sodium ion layered oxide, and the outer shell comprises LaNi with a perovskite structure. x Cr y M z O 3 , wherein 0.2≤x≤0.5, 0.2≤y≤0.5, 0≤z≤0.5, x+y+z=1, and M is selected from at least one transition metal element.
[0036] In the positive electrode material of the embodiment of the present application, La in the shell 3+ with Na + The ionic radius of the materials is similar, and ion exchange reaction on the surface of the materials can significantly increase the overpotential of the surface oxygen evolution reaction and inhibit the production of lattice oxygen, stabilize the valence changes of transition metals during charge and discharge, and improve the stability of the materials.
[0037] In the positive electrode material of the embodiment of the present application, the outer shell includes a perovskite structure (ABO 3) x Cr y M z O 3 , wherein 0.2≤x≤0.5, 0.2≤y≤0.5, 0≤z≤0.5, x+y+z=1, and M is selected from at least one transition metal element. 3 The simultaneous addition of Ni and Cr elements at the B position in the shell can provide the shell with good conductivity and corrosion resistance, thereby improving the structural stability of the positive electrode material while ensuring that the positive electrode material of the sodium ion battery has good conductivity and electrochemical activity.
[0038] When Ni and Cr elements are doped into the B position and other transition metal elements are added at the same time, the shell material can be made high-entropy, and the shell material is more inclined to form a single-phase solid solution, which is beneficial to further improve the structural stability of the shell material, and then improve the structural stability of the positive electrode material.
[0039] In an optional embodiment, M is selected from at least one of Sc, Ti, V, Mn, Fe, Co, Cu, and Zn.
[0040] The stability of perovskite structured materials is related to the tolerance factor t. When M is selected from at least one of Sc, Ti, V, Mn, Fe, Co, Cu, and Zn, the tolerance factor is 0.75≤t≤1.0, and the outer shell is a stable perovskite structure.
[0041] In an optional embodiment, M is selected from at least one transition metal ion having a positive trivalence, for example, M may be at least one of Mn, Fe or Co.
[0042] Trivalent metal ions such as Mn, Fe or Co and Ni 3+ Cr 3+ The ionic radius is similar, and it is not easy to produce lattice distortion after solid solution with Ni and Cr, which is more conducive to improving the stability of the material. At the same time, it can undergo partial redox reactions during the charge and discharge process and provide partial capacity.
[0043] In an optional embodiment, in the positive electrode material, the mass ratio of the shell to the core is 1.0wt% to 3wt%, specifically 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2.0wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt%, 3.0wt% or any value between 1.0wt% and 3.0wt%.
[0044] Reasonable selection of the mass fraction of the shell can form a uniform and continuous shell without reducing the capacity of the positive electrode material.
[0045] In an optional embodiment, the shell thickness is 50 nm to 200 nm, and specifically can be 50 nm, 80 nm, 110 nm, 140 nm, 170 nm, 200 nm or any value between 50 nm and 200 nm.
[0046] The shell has a certain thickness, which can effectively increase the diffusion rate of sodium ions while better isolating the core and the electrolyte, which is beneficial for the positive electrode material to resist the erosion of the electrolyte, thereby improving the discharge specific capacity and capacity retention rate of the positive electrode material. The shell thickness has a certain thickness and can also effectively reduce the surface residual alkali of the positive electrode material, inhibit the gel phenomenon in the battery pulping process and the gas generation phenomenon in the charge and discharge cycle process, and improve the safety and cycle stability of the battery. As the thickness of the shell increases, the effect of the shell on improving stability and reducing residual alkali tends to be stable, so the shell should not be too thick.
[0047] In an optional embodiment, the mass fraction of residual hydroxide in the positive electrode material is less than 0.1wt%, specifically 0.1wt%, 0.09wt%, 0.08wt%, 0.07wt%, 0.06wt%, 0.05wt%, 0.04wt%, 0.03wt%, 0.02wt%, 0.01wt% or any value less than 0.1wt%.
[0048] In an optional embodiment, the chemical formula of the sodium ion layered oxide is Na a Ni i Fe j Mn k N 1-i-j- k O 2 , wherein 0.8≤a≤1.1, 0.2≤i≤0.3, 0.1≤j≤0.2, 0.4≤k≤0.5, and N is selected from at least one of Cu, Zn, Sn, Ti, Co, Al, Zr, Y, Ca, Li, Rb, Cs, W, Ce, Mo, Ba, Mg, Ta, Nb, V, Sc, Sr, and B elements.
[0049] The sodium ion layered oxide in the embodiment of the present application can be selected from commercial products, or can be prepared by a high-temperature solid phase sintering method, and the specific steps include: uniformly mixing a sodium source (sodium carbonate or sodium hydroxide, etc.) and a transition metal source (precursor hydroxide, oxide, carbonate, etc.) at a molar ratio of 0.7-1.2:1.0, heating to 650°C-1100°C at a heating rate of 1-5°C / min under an oxygen-containing atmosphere, calcining for 5-20h, cooling to room temperature, crushing, and sieving with 400 mesh to obtain a material with a chemical formula of Na a Ni i Fe j Mn k N1-i-j-k O 2 of sodium ion layered oxides.
[0050] The embodiment of the present invention also provides a method for preparing a positive electrode material for a sodium ion battery, wherein a first mixture including a core material and a shell material is first calcined to obtain the positive electrode material; wherein the shell material includes LaNi with a perovskite structure x Cr y M z O 3 , wherein 0.2≤x≤0.5, 0.2≤y≤0.5, 0≤z≤0.5, x+y+z=1, and M is selected from at least one transition metal element.
[0051] The sodium ion battery positive electrode material is prepared by a high-temperature solid-phase sintering method, which has a simple process and is easy to operate.
[0052] In an optional embodiment, the positive electrode material satisfies at least one of the following conditions:
[0053] a. The temperature of the first calcination is 400°C-800°C, specifically 400°C, 500°C, 600°C, 700°C or any value between 400°C-800°C; the time is 5h-20h, specifically 5h, 10h, 15h, 20h or any value between 5h-20h;
[0054] b. The heating rate of the first calcination is 1°C / min-5°C / min, specifically 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value between 1°C / min-5°C / min; the atmosphere is an oxygen-containing atmosphere, such as air;
[0055] Appropriate calcination temperature and time are conducive to the shell material being relatively evenly and firmly coated on the core surface, so that during the cycle of the positive electrode material, the shell can be relatively firmly attached to the core surface, which is conducive to improving the stability of the positive electrode material.
[0056] c. The core material comprises a sodium ion layered oxide;
[0057] Optionally, the chemical formula of the sodium ion layered oxide is Na a Ni i Fe j Mn k N 1-i-j-k O 2, wherein 0.8≤a≤1.1, 0.2≤i≤0.3, 0.1≤j≤0.2, 0.4≤k≤0.5, and N is selected from at least one of Cu, Zn, Sn, Ti, Co, Al, Zr, Y, Ca, Li, Rb, Cs, W, Ce, Mo, Ba, Mg, Ta, Nb, V, Sc, Sr, and B;
[0058] d. The M is selected from at least one of Sc, V, Cr, Mn, Fe, Co, and Ni;
[0059] e. The M is selected from at least one transition metal ion having a positive trivalent ion; for example, M may be at least one of Mn, Fe or Co.
[0060] In an optional embodiment, the method for preparing the shell material comprises: mixing metal oxides including La, Ni, Cr and M and performing a second calcination to obtain the LaNi perovskite structure. x Cr y M z O 3 , wherein M is selected from at least one transition metal element;
[0061] Optionally, the temperature of the second calcination is 650°C-1100°C, specifically 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C or any value between 650°C and 1100°C; the time is 5h-20h, specifically 5h, 10h, 15h, 20h or any value between 5h-20h.
[0062] Appropriate calcination temperature and time are beneficial to the LaNi perovskite structure x Cr y M z O 3 formation.
[0063] An embodiment of the present invention further provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in any one of the aforementioned embodiments, or the sodium ion battery positive electrode material prepared by the method for preparing the sodium ion battery positive electrode material described in any one of the aforementioned embodiments.
[0064] An embodiment of the present invention further provides an electrical device, comprising the sodium ion battery described in the aforementioned embodiment.
[0065] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0066] Example 1
[0067] In this embodiment, a sodium ion battery positive electrode material is prepared, wherein the specific preparation method of the core is as follows: according to the chemical formula stoichiometric molar ratio, weigh the corresponding weight of Na 2 CO 3 、NiO、Fe 2 O 3 、MnO 2 and MgO, and then added to the mixer at a speed of 2000r / min and mixed for 3min. The mixed materials were placed in a muffle furnace under air atmosphere at 950℃ for 12 hours, then cooled with the furnace, crushed by a universal crusher, and sieved through 400 mesh to obtain Na 0.9 Ni 0.29 Fe 0.2 Mn 0.45 Mg 0.06 O 2 The layered oxide, SEM image is as follows Figure 1 As shown, the XRD pattern is Figure 4 shown.
[0068] The specific preparation method of the shell is as follows: according to the chemical formula, weigh the corresponding weight of La 2 O 3 , NiO and Cr 2 O 3 , and then add it to the mixer at a speed of 2000r / min and mix for 3min. The mixed materials are placed in a muffle furnace under air atmosphere at a constant temperature of 970℃ for 15 hours, then cooled with the furnace, crushed by a universal crusher, and sieved with 400 mesh to obtain a LaNi 0.5 Cr 0.5 O 3 of perovskite materials.
[0069] The specific preparation method of the positive electrode material of sodium ion battery is as follows: 0.9 Ni 0.29 Fe 0.2 Mn 0.45 Mg 0.06 O 2 and LaNi 0.5 Cr 0.5 O 3 The mixture was mixed at a mass ratio of 50:1, kept at a constant temperature of 650°C for 12 hours in a muffle furnace under air atmosphere, and then cooled with the furnace. The mixture was crushed by a universal grinder and sieved through 400 mesh to obtain the positive electrode material for sodium ion batteries. The SEM images and cross-sectional SEM images are shown in the figure. Figure 2 and 3 As shown, the XRD pattern is Figure 5 shown.
[0070] from Figure 1 and Figure 2 It can be seen that the core material has a relatively rounded single crystal morphology. After coating, the surface of the material has a relatively flat and uniform shell. Figure 3 The average thickness of the shell on the core surface is 100nm. Figure 4 and Figure 5 It can be seen that the core material is O3 phase, and after coating, a peak of perovskite structure appears near 2θ=32.5°. Combining SEM and XRD, it can be seen that the outer shell of the positive electrode material is LaNi with perovskite structure. 0.5 Cr 0.5 O 3 .
[0071] Example 2
[0072] This embodiment prepares a sodium ion battery positive electrode material. The preparation method is basically the same as the preparation method in Example 1. The main difference is that during the preparation of the shell, the corresponding weight of La 2 O 3 、NiO、Cr 2 O 3 and Co 2 O 3 , at a constant temperature of 1000℃, LaNi 1 / 3 Cr 1 / 3 Co 1 / 3 O 3 .
[0073] Example 3
[0074] This embodiment prepares a sodium ion battery positive electrode material. The preparation method is basically the same as the preparation method in Example 2. The main difference is that during the preparation of the shell, the corresponding weight of La 2 O 3 、NiO、Cr 2 O 3 and Mn 2 O 3 , at a constant temperature of 1030℃, LaNi 1 / 3 Cr 1 / 3 Mn 1 / 3 O 3 .
[0075] Example 4
[0076] This embodiment prepares a sodium ion battery positive electrode material. The preparation method is basically the same as the preparation method in Example 2. The main difference is that during the preparation of the shell, the corresponding weight of La 2 O 3 、NiO、Cr 2 O 3 and Fe 2 O3 , at a constant temperature of 980℃, LaNi 1 / 3 Cr 1 / 3 Fe 1 / 3 O 3 .
[0077] Example 5
[0078] This embodiment prepares a sodium ion battery positive electrode material. The preparation method is basically the same as the preparation method in Example 2. The main difference is that during the preparation of the shell, the corresponding weight of La 2 O 3 、NiO、Cr 2 O 3 and Co 2 O 3 , at a constant temperature of 1000℃, LaNi 0.2 Cr 0.3 Co 0.5 O 3 .
[0079] Example 6
[0080] In this embodiment, a sodium ion battery positive electrode material is prepared. The preparation method thereof is substantially the same as the preparation method in Example 2. The main difference is that during the preparation of the sodium ion battery positive electrode material, the core and the shell are mixed and kept at a constant temperature of 550°C.
[0081] Example 7
[0082] In this embodiment, a sodium ion battery positive electrode material is prepared. The preparation method thereof is substantially the same as the preparation method in Example 2. The main difference is that during the preparation of the sodium ion battery positive electrode material, the core and the shell are mixed and kept at a constant temperature of 750°C.
[0083] Example 8
[0084] This embodiment prepares a sodium ion battery positive electrode material, and its preparation method is basically the same as the preparation method of Example 2, the main difference is that in the preparation process of the sodium ion battery positive electrode material, Na 0.9 Ni 0.29 Fe 0.2 Mn 0.45 Mg 0.06 O 2 and LaNi 1 / 3 Cr 1 / 3 Co 1 / 3 O 3 The mass ratio is 50:0.75.
[0085] Example 9
[0086] This embodiment prepares a sodium ion battery positive electrode material, and its preparation method is basically the same as the preparation method of Example 2, the main difference is that in the preparation process of the sodium ion battery positive electrode material, Na 0.9 Ni 0.29 Fe 0.2 Mn 0.45 Mg 0.06 O 2 and LaNi 1 / 3 Cr 1 / 3 Co 1 / 3 O 3 The mass ratio is 50:1.25.
[0087] Example 10
[0088] This embodiment prepares a sodium ion battery positive electrode material. The preparation method is basically the same as the preparation method in Example 2. The main difference is that during the preparation of the shell, the corresponding weight of La 2 O 3 、NiO、Cr 2 O 3 and Sc 2 O 3 , at a constant temperature of 1050℃, LaNi 1 / 3 Cr 1 / 3 Sc 1 / 3 O 3 .
[0089] Embodiment 11
[0090] This embodiment prepares a sodium ion battery positive electrode material. The difference between its preparation method and that of embodiment 2 is that during the preparation of the core, the corresponding weights of Na 2 CO 3 、NiO、Fe 2 O 3 、MnO 2 , CuO, MgO and ZrO 2 , prepared Na 0.95 Ni 0.25 Fe 0.15 Mn 0.41 Cu 0.08 Mg 0.07 Zr 0.04 O 2 .
[0091] Example 12
[0092] This embodiment prepares a sodium ion battery positive electrode material. The difference between its preparation method and that of embodiment 2 is that during the preparation of the core, the corresponding weights of Na 2 CO 3 、NiO、Fe2 O 3 and MnO 2 , prepared Na 0.87 Ni 0.35 Fe 0.17 Mn 0.48 O 2 .
[0093] Comparative Example 1
[0094] The positive electrode material of the sodium ion battery prepared in this comparative example is: Na 0.9 Ni 0.29 Fe 0.2 Mn 0.45 Mg 0.06 O 2 , not coated with a shell, and its preparation method is the same as the preparation method of the core in Example 1.
[0095] Comparative Example 2
[0096] In this comparative example, a sodium ion battery positive electrode material is prepared. The preparation method is basically the same as the preparation method in Example 1. The main difference is that during the preparation of the shell, the corresponding weight of La 2 O 3 and NiO at 920℃ to prepare LaNiO 3 .
[0097] Comparative Example 3
[0098] In this comparative example, a sodium ion battery positive electrode material is prepared. The preparation method is basically the same as the preparation method in Example 1. The main difference is that during the preparation of the shell, the corresponding weight of La 2 O 3 and Cr 2 O 3 , at 930℃, LaCrO 3 .
[0099] Comparative Example 4
[0100] In this comparative example, a sodium ion battery positive electrode material is prepared. The preparation method is basically the same as the preparation method in Example 1. The main difference is that during the preparation of the shell, the corresponding weight of La 2 O 3 , NiO and Co 2 O 3 , at a constant temperature of 950℃, LaNi 0.5 Co 0.5 O 3 .
[0101] Comparative Example 5
[0102] In this comparative example, a sodium ion battery positive electrode material is prepared. The preparation method is basically the same as the preparation method in Example 1. The main difference is that during the preparation of the shell, the corresponding weight of La 2 O 3 Cr 2 O 3 and Co 2 O 3 , at a constant temperature of 980℃, LaCr 0.5 Co 0.5 O 3 .
[0103] Comparative Example 6
[0104] In this comparative example, a sodium ion battery positive electrode material is prepared. The preparation method is basically the same as the preparation method in Example 1. The main difference is that during the preparation of the shell, the corresponding weight of La 2 O 3 、NiO、MnO 2 and Co 2 O 3 , at a constant temperature of 1000℃, LaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 3 .
[0105] Comparative Example 7
[0106] The positive electrode material of the sodium ion battery prepared in this comparative example is: Na 0.95 Ni 0.25 Fe 0.15 Mn 0.41 Cu 0.08 Mg 0.07 Zr 0.04 O 2 , not coated with a shell, and its preparation method is the same as the preparation method of the core of Example 11.
[0107] Comparative Example 8
[0108] The positive electrode material of the sodium ion battery prepared in this comparative example is: Na 0.87 Ni 0.35 Fe 0.17 Mn 0.48 O 2 , not coated with a shell, and its preparation method is the same as the preparation method of the core of Example 12.
[0109] The residual hydroxide content and pH of the positive electrode materials prepared in the above examples and comparative examples were tested, and the test method was as follows:
[0110] (1) pH value test: 5 g of sample and 50 g of deionized water were placed in a 250 mL beaker. After magnetic stirring for 10 min, pH was tested using a pH meter.
[0111] (2) Residual hydroxide test: 10 g of sample and 100 g of anhydrous ethanol were placed in a 250 mL beaker. After magnetic stirring for 20 min, the mixture was filtered and 50 g of the clear filtrate was placed in a 100 mL beaker. Potentiometric titration was performed using a hydrochloric acid standard solution.
[0112] The test results are shown in Table 1.
[0113] Sodium ion battery preparation
[0114] The positive electrode material prepared in the above embodiments and comparative examples is mixed evenly with the conductive agent and the binder in NMP solvent, and then coated on aluminum foil. After that, it is baked, rolled, and sliced to form a positive electrode plate. Finally, the positive electrode plate is assembled with a diaphragm, a sodium sheet, and a gasket to form a sodium ion button battery. The prepared sodium ion button battery is tested using a battery test cabinet. The test conditions are: sodium sheet negative electrode, voltage range of 2.0-4.2V, test temperature of 25±1°C. The battery performance test results are shown in Table 1.
[0115] Table 1
[0116]
[0117] As shown in Table 1, compared with Comparative Example 1, Examples 1-10 coated with LaNi x Cr y M z O 3 After that, the specific capacity, rate performance and cycle stability of the battery are improved. Compared with Example 1, the LaNi coated 1 / 3 Cr 1 / 3 Co 1 / 3 O 3 、LaNi 1 / 3 Cr 1 / 3 Mn 1 / 3 O 3 、LaNi 1 / 3 Cr 1 / 3 Fe 1 / 3 O 3 、LaNi 1 / 3 Cr 1 / 3 Sc 1 / 3 O 3 After the coating temperature or coating amount is changed in Examples 6-9, the specific capacity, rate performance and cycle stability are all maintained at a relatively good level, but the comprehensive performance is slightly lower than that in Examples 2-5.3+ Cr 3+ Co, which has a closer ionic radius 3+ , Fe 3+ , Mn 3+ When M is Sc 3+ The overall performance is better.
[0118] In addition, it can be seen from Table 1 that the residual alkali of the material is significantly reduced after coating, which is beneficial to inhibit the gel phenomenon in the battery pulping process and the gas generation phenomenon in the charge and discharge cycle process, and improve the safety and cycle stability of the battery.
[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A sodium ion battery positive electrode material, characterized in that: It includes a core and a shell, wherein the core is a sodium ion layered oxide, and the shell includes LaNi with a perovskite structure. x Cr y M z O3, wherein 0.2≤x≤0.5, 0.2≤y≤0.5, 0≤z≤0.5, x+y+z=1, and M is selected from at least one transition metal element.
2. The sodium ion battery positive electrode material according to claim 1, characterized in that M is selected from at least one of Sc, Ti, V, Mn, Fe, Co, Cu, and Zn.
3. The sodium ion battery positive electrode material according to claim 1, characterized in that M is at least one selected from transition metal ions having a positive valence of three.
4. The sodium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The mass ratio of the shell to the core is 1.0wt% to 3wt%; (2) The thickness of the shell is 50 nm to 200 nm; (3) The mass fraction of residual hydroxide in the positive electrode material is less than 0.1 wt %.
5. The sodium ion battery positive electrode material according to claim 1, characterized in that The chemical formula of the sodium ion layered oxide is Na a Ni i Fe j Mn k N 1-i-j-k O2, wherein 0.8≤a≤1.1, 0.2≤i≤0.3, 0.1≤j≤0.2, 0.4≤k≤0.5, and N is selected from at least one of Cu, Zn, Sn, Ti, Co, Al, Zr, Y, Ca, Li, Rb, Cs, W, Ce, Mo, Ba, Mg, Ta, Nb, V, Sc, Sr, and B elements.
6. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: The first mixture including the core material and the shell material is first calcined to obtain the positive electrode material; wherein the shell material includes LaNi with a perovskite structure x Cr y M z O3, wherein 0.2≤x≤0.5, 0.2≤y≤0.5, 0≤z≤0.5, x+y+z=1, and M is selected from at least one transition metal element.
7. The method for preparing a positive electrode material for a sodium ion battery according to claim 6, characterized in that: The positive electrode material satisfies at least one of the following conditions: a. The first calcination temperature is 400 ℃-800 ℃, and the time is 5h-20h; b. The heating rate of the first calcination is 1°C / min-5°C / min; c. The core material comprises a sodium ion layered oxide; Optionally, the chemical formula of the sodium ion layered oxide is Na a Ni i Fe j Mn k N 1-i-j-k O2, wherein 0.8≤a≤1.1, 0.2≤i≤0.3, 0.1≤j≤0.2, 0.4≤k≤0.5, and N is selected from at least one of Cu, Zn, Sn, Ti, Co, Al, Zr, Y, Ca, Li, Rb, Cs, W, Ce, Mo, Ba, Mg, Ta, Nb, V, Sc, Sr, and B; d. The M is selected from at least one of Sc, V, Cr, Mn, Fe, Co, and Ni; e. The M is selected from at least one transition metal ion having a positive trivalence.
8. The method for preparing the positive electrode material for a sodium ion battery according to claim 6, characterized in that: The preparation method of the shell material comprises: mixing metal oxides including La, Ni, Cr and M and performing a second calcination to obtain the LaNi perovskite structure. x Cr y M z O3, wherein M is selected from at least one transition metal element; Optionally, the second calcination is performed at a temperature of 650° C.-1100° C. and for a time of 5 h-20 h.
9. A sodium ion battery, characterized in that: The invention relates to a sodium ion battery positive electrode material comprising the positive electrode material of any one of claims 1 to 5, or a sodium ion battery positive electrode material prepared by the method for preparing the positive electrode material of a sodium ion battery of any one of claims 6 to 8.
10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.
Citation Information
Patent Citations
Anode material for lithium ion battery and synthetic method thereof
CN103187568A
Perovskite type conductor material coated ternary positive electrode material, preparation method thereof and lithium ion battery
CN111933910A
Coated positive electrode material for sodium-ion battery and preparation method of coated positive electrode material
CN117117167A
Sodium ion layered oxide positive electrode material coated with inorganic acid sodium salt and preparation method of sodium ion layered oxide positive electrode material
CN117810426A
Low-gas-production positive electrode material as well as preparation method and application thereof
CN119170764A